A ground robotic system for crops and soil monitoring and data collection in New Mexico chile pepper farms - Jordan Linford; Mahdi Haghshenas-Jaryani (Discover Agriculture, 2024)
Abstract This work presents the development and system integration of a ground agricultural mobile manipulator robot that is capable of traversing a field in order to monitor the health of the field and crops. The robotic platform consists of a 4-wheeled drive base rover that has a 6 degrees of freedom (DOF) robotic manipulator attached to it, which is equipped with a multitude of sensors that are used for navigation, crop inspection, and soil monitoring. To accurately measure the moisture of the soil using the moisture probe, the insertion process is very important, as the probe has to be inserted to the correct depth and be flush with the soil. It is for this reason, that the insertion process is difficult, as the field can be rough and uneven terrain. Utilizing a camera attached to the wrist of the robotic manipulator, the soil insertion process can be adjusted to more accurately insert the soil probe into the terrain with a varying degree of slopes. Along with detecting the slope of the soil to perform an accurate soil insertion, the robotic system is capable of detecting plants in various stages of development, and capture images to visually determine the crops health. The successful operation of the robot for in-situ soil measurements, crops image capturing, plant’s physical characteristics detection, and an autonomous soil slope alignment for sensor insertion have been demonstrated.